NSRG-26. ENDOSCOPIC RESECTION OF INTRAVENTRICULAR LESIONS USING AN ENDOSCOPIC ULTRASONIC ASPIRATOR. Issue 2 (22nd June 2018) - Burford, Charlotte; Kalyal, Nida; Hanrahan, John; Ansaripour, Ali; Al-Faiadh, Wisam; Oviedova, Anna; Ghimire, Prajwal; Bleil, Cristina; Zebian, Bassel
Abstract: INTRODUCTION: The use of the endoscopic ultrasonic aspirator for the management of intraventricular tumours is still in its infancy. We share our early experience using the aspirator in the management of intraventricular, paraventricular and suprasellar tumours. SUBJECTS: 19 patients (10 males, 9 females) underwent 22 operations with the endoscopic ultrasonic aspirator. Ages ranged from 6 months to 86 years. Tumour types included: a choroid plexus papilloma (grade II), an infiltrative glioma (grade II), an intraventricular meningioma (grade I-II), a diffuse glioma (grade II-III), three craniopharyngiomas, an anaplastic ependymoma (grade III), two glioblastomas (grade IV), an immature teratoma, 2 gangliogliomas (grade I), a choroid plexus cyst, a central neurocytoma (grade II), a pineocytoma (grade I), a metastasis (lung primary), a subependymoma (grade I) and a pilocytic astrocytoma with pilomyxoid features (grade I). RESULTS: A monoportal approach guided by neuronavigation was used in all patients. Of the 22 procedures, 18 were carried out in patients with hydrocephalus. In 6 procedures a total or near-total resection was achieved. Tumour resection was limited by tumour location, size and consistency as well as instrumentation. CONCLUSION: The endoscopic ultrasonic aspirator is a powerful addition to our neuro-endoscopic armamentarium and with further development, endoscopic total resections may become more commonplace.